Parâmetros comportamentais e fisiológicos em peixes-zebra adultos expostos a cetamina - Michelotti, Paula (2020)
Ketamine is an anesthetic widely used in human and veterinary clinic and also as a drug of abuse. It has dissociative anesthetic property that in subanesthetic doses induces analgesia. Although ketamine displays anxiolytic and antidepressant properties, it may induce pro-psychosis and hallucinogen effects, as well as stereotypic behaviors following acute administration at sub-anesthetic doses. Zebrafish (Danio rerio) is a small teleost widely used in behavioral neuroscience research, because it presents conservation in physiology, characterized neurotransmitters and genome completely sequenced and similar to humans (70%). Considering that many neuropsychiatric diseases are related to changes in behavioral and biochemical parameters, the study of the effects promoted by subanesthetic doses of ketamine in zebrafish is relevant. Thus, we investigated the effects of ketamine exposure for 20 min (0, 2, 20 or 40 mg/L) acutely and repeatedly (7 days) on aggression, locomotion, stereotyped behavior, memory consolidation, and anxiety. In addition, we analyze whole-body cortisol levels and brain acetylcholinesterase activity in adult zebrafish. Results of acute exposure show an increase in the phenotypes of aggression induced by the mirror at a concentration of 2 mg/L and a reduction in the concentration of 20 and 40 mg/L; we also observed an increase in stereotyped behavior of circular swimming in fish exposed to concentration of 40 mg/L, and locomotor alterations due to hyperlocomotion in concentrations of 20 and 40 mg/L. Memory consolidation is impaired at concentration of 40 mg/L. None of the doses altered the activity of acetylcholinesterase. The results of repeated exposure show that behavioral parameters such as locomotion, aggression and anxiety, along with whole-body cortisol levels and acetylcholinesterase activity were not altered by exposure to Ketamine. However, animals exposed to a concentration of 40 mg/L showed stereotyped behavior. In short, we found that the behavioral changes induced by ketamine depend on the behavioral task and the tested dose. Taken together, we can suggest that this animal model may be useful to investigate the effects of subanesthetic ketamine concentrations on behavioral parameters; however, intermediate concentration in relation to that used in this study, other behavioral tasks, as well as other exposure intervals need to be studied.